Refractory Chylothorax and Ventricular Hypertrophy Treated with Trametinib in a Patient with Noonan Syndrome: 18-Month Follow-Up - Antonia Pascarella; Giuseppe Limongelli; Alessandro De Falco; Elia Marco Paolo Minale; Giangiacomo Di Nardo; Giovanni Maria Di Marco; Geremia Zito Marinosci; Giorgia Olimpico; Paolo Siani; Daniele De Brasi (Children)
RASopathies are a group of genetic syndromes caused by germline mutations in genes involved in the RAS/Mitogen-Activated Protein Kinase signaling pathway, which regulates cellular proliferation, differentiation, and angiogenesis. Despite their involvement at different levels of this pathway, RASopathies share overlapping clinical phenotypes. Noonan syndrome is the most prevalent RASopathy, with an estimated incidence of 1 in 2500 live births, and it is typically inherited in an autosomal dominant manner, with 50% of cases involving gain-of-function mutations in the PTPN11 gene. De novo mutations are common, accounting for 60% of cases. The phenotype of Noonan syndrome includes characteristic facial and physical features, congenital cardiac defects, lymphatic and cerebrovascular anomalies, renal malformations, hematological abnormalities, developmental issues, and an increased risk of cancer. Severe congenital cardiac defects and lymphatic abnormalities significantly impact prognosis, contributing to increased morbidity and mortality. Recent therapeutic advancements have introduced trametinib, an MEK1/2 inhibitor, for treating Noonan syndrome patients with severe cardiac and lymphatic complications. To assess its efficacy, here, we present a case of a newborn with Noonan syndrome who exhibited refractory chylothorax, ventricular hypertrophy, and pulmonary stenosis who was treated with trametinib. The patient demonstrated significant improvement in chylothorax and left ventricular hypertrophy, though pulmonary stenosis persisted. This case further confirms trametinib’s potential as a therapeutic option for severe Noonan syndrome complications, emphasizing the need for further clinical trials to optimize treatment protocols and evaluate long-term outcomes.